Teologi Kesia-siaan Menurut Kitab Pengkhotbah - Gebriel Lumban Tobing; Roselita Sinaga; Michael Juan Nababan (Publisher STPKat, 2024)
The preacher highlights the emptiness and transience of the materialistic world as well as the importance of man's relationship with God to find true meaning in life. This book emphasizes that living without fear of God is considered futile, and only by surrendering to Allah can a person find true peace and happiness. Through Christ's death and resurrection, vanity can be rejected and life can be directed to eternal things.